2020
DOI: 10.1007/s11590-020-01594-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical formulations and improvements for the multi-depot open vehicle routing problem

Abstract: The multi-depot open vehicle routing problem (MDOVRP) is a hard combinatorial optimization problem belonging to the vehicle routing problem family. It considers vehicles departing from different depots to deliver goods to customers without requiring to return to the depots once all customers have been served. The aim of this work is to provide a new two-index-based mathematical formulation for the MDOVRP as well as enhancements on alternative sub-tour elimination constraints. Through numerical experiments, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They compared the algorithm with several other algorithms and found that OVRP_SAICA performs better than all of them in solving the OVRP. Lalla-Ruiz and Mes ( 2021 ) proposed a two-index-based mathematical formulation for the MDOVRP. Also, they presented a memetic algorithm (MA) for solving the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They compared the algorithm with several other algorithms and found that OVRP_SAICA performs better than all of them in solving the OVRP. Lalla-Ruiz and Mes ( 2021 ) proposed a two-index-based mathematical formulation for the MDOVRP. Also, they presented a memetic algorithm (MA) for solving the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the variant of the MDVRP that considers open routes (MDVORP) problem was introduced in the literature by Tarantilis and Kiranoudis (2002) to tackle a distribution problem of fresh meat, considering a homogeneous fleet of vehicles. Since then, relevant studies such as (Lalla-Ruiz et al, 2016;Lalla-Ruiz & Mes, 2020;Liu et al, 2014;Soto et al, 2017) proposed mathematical formulations and efficient metaheuristic algorithms to handle this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The battery manufacturing industry is one of the application areas for VRP (as a two-echelon problem), and in [ 41 ], the green transportation problem for this area is considered a two-echelon problem. At the first echelon, the green transportation with inventory problem is discussed, and at the second echelon, the simultaneous pickup and delivery of capacitated multidepot (distribution and collection center) heterogeneous green vehicle routing problem (MDHVRPSPD) is the main focus (heterogeneous vehicles for the multidepot routing problem are discussed in [ 34 ] with a definition of open location (MD-OLRP), and in [ 26 ], the multidepot open vehicle routing problem (MDOVRP) is analyzed with state-of-the-art formulations). Three objectives are selected and integrated in the problem: carrying cost, transportation cost and carbon emission cost (as a single-objective problem).…”
Section: Introductionmentioning
confidence: 99%